Regional and sectoral assessment on climate-change in Pakistan: Social norms and indigenous perceptions on climate-change adaptation and mitigation in relation to global context. (1st November 2018) - Hussain, Mudassar; Liu, Guijian; Yousaf, Balal; Ahmed, Rafay; Uzma, Faiza; Ali, Muhammad Ubaid; Ullah, Habib; Butt, Abdul Rahman
Abstract: Climate change has extremely damaged the whole world, particularly South Asian countries because common residents in this region are considered highly vulnerable to climate change impacts whereas their common awareness to adapt and mitigate these impacts is very low. Pakistan is one of the most important South Asian countries and has been affected tremendously through several impacts namely; temperature rise, drought, pest-diseases, health issues, seasonal and lifestyle change and it has the potential to continue doing so in future. We conducted a survey to explore the adaptation and mitigation alertness to climate change among all provinces and areas (urban, peri-urban and rural) of Pakistan from general public since they are directly affected by climate change. In Pakistan, climate change is essentially caused by greenhouse gas (GHG) emissions and the foremost sources of rise in the GHG emissions are human activities, such as deforestation and emissions from various sectors; transportation, industrialization, urbanization, waste, agriculture livestock & forestry and energy usage. All of these have a significant impact on climate change in all areas and provinces. The study determines that all the areas in Pakistan played an increased role in climate change, but rural, peri-urban, and small cities turned out to be in worst situation due to lack of attention and ignorance. Datum produced from this study can pave a way for assisting in preparing, instructing, and guiding national and international decision makers in order to upgrade the levels of adaptation and mitigation policy making and its implementation in South Asia specially and at global scale generally. Graphical abstract: Image 1